Refined numerical study on the effect of grouting plumpness on bearing behavior of pipe roof - Shi, Yufeng; Hu, Menghao; Zhang, Tao; Chen, Xiangsheng; Zhou, Yuhang; Min, Shichao; Jiang, Yalong (Frontiers in Materials, 2022)
Pre-supported pipe roof grouting is difficult to be satisfied due to various influences, which may have an impact on its bearing characteristics. In order to determine the impact of grouting plumpness on the bearing behavior of pipe roof, based on the preliminary experimental research a refined numerical model that takes into account the bonding between the steel pipe and cement mortar was established in this paper. It was used to analyze the bending moment-deflection curve, variation laws of ultimate bearing capacity coefficient, and disengagement rate of pipe roof under different grouting plumpness. Meanwhile, the working conditions of reinforcement and casing in the pipe were conducted. The results show that compared with full grouting, the ultimate bearing capacity of the grouting pipe roof, pipe roof with reinforcement bundles and casing pipe decreases by 4.6%, 5.2%, and 4.8% respectively when grouting incompleteness is 2%, and decreases by 35.3%, 40.4%, and 37.1% respectively, when grouting incompleteness rises to 25%; The ultimate bearing capacity of the pipe roof can be greatly enhanced by adding reinforcement bundles and casing pipe, and the increases of this case is 7.7%–18.3%, 31.4%–51.6%, respectively; The disengagement rate of pipe roof and mortar under the same load increases with the increase of grouting incompleteness, which growing relatively slowly when the grouting incompleteness is less than 2%, and develops rapidly when it is 2%–30%, while growing little when it is more than 30%. Under the same grouting incompleteness, adding reinforcement bundles and casing pipe in the pipe roof can effectively reduce its debonding rate and the latter has a better effect, and the corresponding disengagement rate is 62.8%–97.9% and 29.1%–91.9% of the grouting pipe roof respectively.